How do we know that the Earth spins around its axis? - Pendrill, Ann Marie ; 0000-0002-1405-6561 (Physics Education, 2008)
A carousel gives possibilities to explore physics in rotating systems and to gain first-hand experience of methods to measure rotation, without the need for an external reference. This paper discusses the Foucault pendulum, as well as the sideways deflection of horizontally and vertically moving objects in a rotating system. These experiments lay the foundation for an understanding of ways to demonstrate that the Earth spins around its axis.